The impact of childhood adversity on the persistence of psychotic symptoms: a systematic review and meta-analysis. Issue 12 (September 2015) - Trotta, A.; Murray, R. M.; Fisher, H. L.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Evidence suggests that childhood adversity is associated with the development of psychotic experiences (PE), psychotic symptoms and disorders. However, less is known regarding the impact of early adversity on the persistence of PE and clinically relevant psychosis. Thus we conducted a systematic review of the association between childhood adversity and the course of PE and symptoms over time. Method A systematic search of Medline, EMBASE and PsychINFO databases was undertaken to identify articles published between January 1956 and November 2014. We included studies conducted on general population samples, individuals at ultra-high risk (UHR) of psychosis, and patients with full-blown psychotic disorders. A meta-analysis was performed on a subgroup. Results A total of 20 studies were included. Of these, 17 reported positive associations between exposure to overall or specific subtypes of childhood adversity and persistence of PE or clinically relevant psychotic symptoms. A meta-analysis of nine studies yielded a weighted odds ratio of 1.76 [95% confidence interval (CI) 1.19–2.32, p < 0.001] for general population studies and 1.55 (95% CI 0.32–2.77, p = 0.007) for studies conducted using clinical populations. Conclusions The available evidence is limited but tentatively suggests that reported exposure to adverse events in childhood is associated with persistence of PE and clinically relevant psychotic symptoms. This partially strengthens the case for addressing the consequences of early adversity in individuals presenting with psychotic phenomena to improve long-term outcomes. However, the heterogeneity of studies was high which urges caution in interpreting the results and highlights the need for more methodologically robust studies.